2022
DOI: 10.3390/ncrna8010013
|View full text |Cite
|
Sign up to set email alerts
|

FibroDB: Expression Analysis of Protein-Coding and Long Non-Coding RNA Genes in Fibrosis

Abstract: Most long non-coding RNAs (lncRNAs) are expressed at lower levels than protein-coding genes and their expression is often restricted to specific cell types, certain time points during development, and various stress and disease conditions, respectively. To revisit this long-held concept, we focused on fibroblasts, a common cell type in various organs and tissues. Using fibroblasts and changes in their expression profiles during fibrosis as a model system, we show that the overall expression level of lncRNA gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 88 publications
0
10
0
2
Order By: Relevance
“…Xu et al revealed that LINC01711 was upregulated in esophageal carcinoma and associated with malignant phenotypes and poor prognosis [ 42 ]. Existing literature had shown that LINC01711 was included in the prognostic model and may play essential roles in malignant progression of ESCC, triple negative breast cancer and fibrosis [ 43 , 44 , 45 ]. Shi et al reported that AC011997.1 was considered as a prognostic risk factor in ESCC [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al revealed that LINC01711 was upregulated in esophageal carcinoma and associated with malignant phenotypes and poor prognosis [ 42 ]. Existing literature had shown that LINC01711 was included in the prognostic model and may play essential roles in malignant progression of ESCC, triple negative breast cancer and fibrosis [ 43 , 44 , 45 ]. Shi et al reported that AC011997.1 was considered as a prognostic risk factor in ESCC [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…As for fibrotic lncRNAs, especially in the cardiopulmonary system and its associated diseases, the number of functionally characterized fibrotic lncRNAs is scarce. To assist in the identification of lncRNAs expressed in fibroblasts and involved in fibrosis-especially in cardiac and pulmonary fibrosis-we recently released the web application FibroDB [86] (https://rnamedicine.shinyapps.io/FibroDB/, accessed on 12 July 2022).…”
Section: Discussionmentioning
confidence: 99%
“…0.05) changed their abundance upon TGFb1 treatment (Figure 3A). Pathway enrichment analysis of these significantly regulated proteins showed enrichment of pro-fibrotic pathways 22,23 such as ECM organisation, Cell Adhesion and Tissue morphogenesis (Figure 3B). TGFb1 treatment caused a significant upregulation of pro-fibrotic ECM proteins 24 such as COL1, COL3, FN1, THBS1, FBN1 (Figure 3B) and an upregulation of enzymes that aid the polymerization of collagens in ECM such as BMP1, LOXL2, COL5 25 .…”
Section: Dxm Blocks Collagen Type 1 and Like Cargoes In The Endoplasm...mentioning
confidence: 99%